Plasma IL-17A is increased in patients with critical MIS-C and associated to in-hospital mortality - de Farias, Emmerson C. F.; Nascimento, Luciana M. P. P. do; Pavão Junior, Manoel J. C.; Pavão, Dalila C. A.; Pinheiro, Ana P. S.; Pinheiro, Andreza H. O.; Alves, Marília C. B.; Ferraro, Kíssila M. M. M.; Aires, Larisse F. Q.; Dias, Luana G.; Machado, Mayara M. M.; Serrão, Michaelle J. D.; et al. (Frontiers in Immunology, 2025)
BackgroundMultisystem inflammatory syndrome in children (MIS-C) is a rare and severe post-COVID-19 complication with multiple phenotypes.ObjectivesThe aim of this study is to study inflammatory biomarkers (cytokines and oxidative stress) in critical MIS-C patients and to observe if there is association between these biomarkers and mortality.MethodsA single-center prospective study enrolled patients with MIS-C (with positive molecular test), aged between 1 month and 18 years of age. Data was collected from 20 pediatric intensive care unit (PICU)’s bed. Inflammatory biomarkers (cytokines and oxidative stress markers) were performed on day 1 and 3 after hospitalization. Survival rate was calculated, and Kaplan-Meier curves were plotted. Univariate and multivariate Cox regression analyses were conducted. The ROC (Receiver Operating Characteristic) curve analysis was performed.Results and conclusionsA total of 41 patients out of 109 patients admitted at PICU with suspected MIS-C during the study period were included, of which 33 (80.5%) were male, 9 (22%) were under one year old, and 30 (73.2%) presented comorbidities. Among them, 16 (39%) did not survive. The mean survival time was shorter in patients with higher levels of IL-17A (≥ 19.71 pg/mL) on day 1 (115 vs 323 days, p = 0.004). Higher levels of IL-17A on day 1 were associated with mortality in both the crude model (HR 1.03, CI95% 1.004-1.057, p = 0.022) and the adjusted model (HR 1.043, CI95% 1.013-1.075, p = 0.012). ROC analysis revealed a cut-off value for the IL-17A of 14.32 pg/ml. The other immunological and inflammatory markers did not demonstrate an association with survival (p>0.05). Our findings suggest that patients with high levels of IL-17A are at greater risk for death.